Application research of wavelet threshold noise reduction in coal mine voice communicatio - ZHANG Miaofei; ZHANG Jianying; XU Changsheng (Gong-kuang zidonghua, 2014)
According to characteristics of high-noise environment in underground coal mine, the paper put forward a new method which adds a wavelet threshold noise reduction module to voice communication terminals. The method improves soft and hard threshold of wavelet threshold noise reduction method, and constructs a new threshold function. The new function varies through a variable between soft and hard wavelet threshold function, so as to reduce the negative impact. The theoretical analysis results show that the application of wavelet threshold noise reduction can significantly improve quality of phone call and coal mine voice communication system.